(3LGeY GdHjGf Yf JChjd Bi GdbQBfs - (3eMeO Hf LQjQ Hf jRjO GdWHQj , GHf LQjQ, CHh LYaQ, J (B310 (3g` s ((3HjGf Hf YHO Gdedc Hf HjGf Hf eMeO GdMfai s)
(3ChdgG (B:s
(3GdMeO ddg GdPi MLHJ GdCdHGH HOGFY Mceg CeG HYO aEf ef LSje eG NU Gddg Hg Ceg fHjfG eMeO Udi Gddg Ydjg hSde ef GdaVjdI hTQage s
(3BNQgG (B:s
(3hde jbQC HJQc GdJfhjf ajg hESbGW GdCda efg EdG ef dG jLhR GdGYJQGV Hg Ydi GdMLI ajeG LGAJ Hg ef GdbQGAI eSJajVkG HjfgG hGddg CYde HGdUhGH Je GdeLdO GdChd s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B69 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B147s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI HGdQHGW (B(299(3b(B) s
Keywords: (3GdJaSjQ hYdhe GdbQBfs